Phenotypic Characterization of Sulfolobus islandicus Strains Lacking the B-Family DNA Polymerases PolB2 and PolB3 Individually and in Combination - Bohall, Peter B.; Bell, Stephen D. (Frontiers in Microbiology, 2021)
Across the three domains of life, B-family DNA polymerases play a variety of roles in both DNA repair and DNA replication processes. We examine the phenotypic consequences of loss of the putative repair polymerases PolB2 and PolB3 in the crenarchaeon Sulfolobus islandicus. We detect a modest growth advantage when cells lacking the polymerase are grown in unperturbed conditions. Further, we observe a striking insensitivity of the mutant lines to acute treatment with the oxidizing agent, hydrogen peroxide. In addition, cells lacking PolB3 show enhanced sensitivity to the DNA damaging agent 4-NQO. Our data therefore suggest that these non-essential DNA polymerases may influence DNA repair pathway choice in these hyperthermophilic aerobes.